Analysis on The Effect of Groyne Type Impermeable Placement on Sediment Distribution in Lariang River Bend - Prasetyo, Wahyu; Juwono, Pitojo Tri; Sisinggih, Dian (Fakultas Teknik UB, 2021)
Sedimentation and erosion caused by differences in discharge is a problem that often occurs at river bends. One of the functions of placing the groyne is to reduce the river flow velocity along the riverbank, accelerate sedimentation, and ensure the embankment or river bank's safety against scouring. This study aimed to determine the distribution of current velocity, distribution of riverbed shear stress, and sediment distribution to the effect of groyne placement. There are 7 (seven) simulation models used to get the most effective groyne placement. From the model simulation results by adding a groyne building on the river's outer bend for the simulation model scenario 2 to scenario 7, the largest sedimentation production is in scenario 3, namely the height of riverbed sediment deposits 230 hours of 1.094 m. Furthermore, the groyne building's effective placement is determined based on a maximum change in the riverbed scenario. In scenario 3, the placement and dimensions of the groyne length of 17.5 m; distance between groyne 24.4 m; the groyne is inclined upstream in the direction of flow 10Â°.